Follicular histomorphometry and evaluation of ovarian apoptosis in queens of different age groups - de Carvalho, Isadora Resende [UNESP]; Denadai, Daniela Scantamburlo [UNESP]; Trevisan, Juliane Teramachi [UNESP]; Mendes, Heloisa Maria Falcão [UNESP]; Perri, Sílvia Helena Venturoli [UNESP]; Monteiro, Cristina Maria Rodrigues [UNESP]; Ferreira, Joana Zafalon [UNESP]; Feliciano, Marcus Antonio Rossi [UNESP]; Pierucci, Julia Cestari [UNESP]; Vicente, Wilter Ricardo Russiano [UNESP]; de Koivisto, Marion Burkhardt [UNESP] (Universidade Federal do Rio Grande do Sul, 2018)
Background: In humans and bitchs the age is another factor that may affect the size of ovarian structures, verifying alterations in the quality of the pool and size of follicular structures, which can compromise the use of these structures for in vitro maturation. There are no reports correlating the morphometric characteristics of the follicles and ovarian apoptosis at different ages in cats. The aim of this study was to evaluate the histomorphometric parameters of follicular growth and the relationship with the occurrence of apoptosis in ovarian tissue of young, adult and senile queens. Materials, Methods & Results: Eighteen domestic queens, multiparous, of different breeds and age groups were used in this study and divided into three groups according to their ages: five months to one year - young; (7.8 ± 1.0 months); one to six years - adults (2.8 ± 0.5 years); and more than six years - senile (8.0 ± 0.9 years). Vaginal cytology was performed in order to characterize the estrous phase associated with plasma concentrations of progesterone. The morphology and percentage of the vaginal epithelium cells were evaluated and queens were classified into estrous and non-estrus and plasma concentrations of progesterone were determined. Ovarian samples were collected after ovariohysterectomy to routine histological processin and all follicles were counted and categorized into two groups, non-atresic and atresic. The mean follicular and oocyte diameters were calculated between the measurement of the largest diameter and perpendicular diameter. The relationship between follicle and oocyte were determined using the measurements of diameter, area and perimeter. The apoptotic cells were detected and cells were considered positive when TUNEL reaction was detected. The morphometric index of 1039 follicles were evaluated. Primordial follicles in young animals showed larger diameter, follicular area and perimeter than the structures of adult queens, as well as the unilaminar primary follicles of the same group were larger compared with senile animals (P < 0.05). Comparing adult and younger queens, the first showed a significant decrease of oocyte diameter in primary and unilaminar primary follicles, as well as oocyte area and perimeter (P < 0.05). The values for follicular diameter, oocyte area and perimeter for multilaminar primary, secondary and pre-ovulatory structures did not present statistical differences between the groups (P > 0.05). For the pre-ovulatory follicles there was no positive correlation between the oocyte growths regarding the follicles (P > 0.05). Only in senile animals positive markers for apoptosis were identified in nuclei of primordial follicles. No significant differences concerning the number of follicles and Tunel positive cells were observed between groups (P > 0.05). Discussion: Considering the importance of this study for greater knowledge in the basic aspects for reproductive biotechnologies, we verified that secondary follicles showed the largest diameters and younger animals the largest values for diameter, area and perimeter, suggesting that this age group could be ideal for the use and manipulation of oocytes. The process of follicular atresia is characterized by the occurrence of apoptosis, or programmed cell death when the organism begins to efficiently eliminate dysfunctional cells. The study of follicular apoptosis in small animals, especially in cats, is very important for the development of reproduction biotechnologies. Phenomenon of apoptosis showed no relationship with age in queens, occurring in a physiological, continuous and proportionate manner considering the number of non-dominant follicles involved in each estrous cycle.
Keywords: Feline; Follicle; Reproduction